Lesson Study to Improve Teacher’s Ability in Scientific Publication of Sustainable Profession Development - Irmawanty, Irmawanty; Syarif Sumantri, Mohamad; Jafar, M. (Opción, 2019)
The Indonesian government has issued a policy on Sustainable Profession De- velopment to improve the professional capabilities of teachers consisting of three components of self-development, scientific publication, and innovation. Despite being part of the professionalism assessment of teachers, but there are still some obstacles in fulfilling these three components, especially in scientific publications due to lack of knowledge and research skills and low motivation to do research. This paper aims to test the process of implementing Sustain- able Profession Development through study lessons in improving teacher’s scientific writing skills, program effectiveness, and evaluating the success of this lessons study program. The research method was a qualitative descriptive with a case study approach. This research was conducted in Serang and Cil- egon, especially in KKG (teacher working group) Madrasah Ibtidaiyah. The subject of this research was the teacher as a member of KKG. Data was col- lected through observations, interviews, documentation, and questionnaires. Data was collected by creating tabulation, coding, interpreting, and display- ing. Based on the results of the study, it can be concluded that the lesson study was effectively used for Sustainable Profession Development activities in im- proving teacher skills in writing and presenting scientific publications. Teach- ers were motivated to participate in this activity because learning activities use an active learning approach in the teacher Working Group as their pro- fessional learning community.